We Are (a Measurable) Family: Affect and Audit in a Toronto HIV/AIDS Service Organisation - Murray, David A.B. (Anthropologica, 2020)
To celebrate its 30th anniversary, a Toronto HIV/AIDS service organisation (HASO) held an event called “Family of HIV” at its annual general meeting in 2017. A drag queen’s performance of the popular gay anthem “We Are Family” and a statement of “love” for the organisation from two clients followed regular annual meeting items like the auditor’s report and election of board directors. These actions created a complex affective and bureaucratic arrangement for an organisation formed through grassroots activism by and for a historically marginalised group (gay men infected with HIV), but that now serves a diverse group of HIV-positive people and is funded through state and private sectors, and is thus enmeshed in a set of obligations and responsibilities to various scales of stakeholders, including local, provincial and national health and welfare agencies. This article argues that the performance of family at the annual meeting privileges a particular affective arrangement of relationships between full-time staff, clients and volunteers that, not coincidentally, occurs in a bureaucratic culture emphasising data as a measurement of value and efficiency. This results in a closely surveilled form of family produced through dense personal and bureaucratic entanglements of regulation, alienation, care, conflict and anxiety.